Evaluating the use of oral pre-exposure prophylaxis among pregnant and postpartum adolescent girls and young women in Cape Town, South Africa - Khadka, Nehaa; Gorbach, Pamina M.; Nyemba, Dorothy C.; Mvududu, Rufaro; Mashele, Nyiko; Javanbakht, Marjan; Nianogo, Roch A.; Aldrovandi, Grace M.; Bekker, Linda-Gail; Coates, Thomas J.; Myer, Landon; Joseph Davey, Dvora L. (Frontiers in Reproductive Health, 2023)
Background Adolescent girls and young women (AGYW) in South Africa are at a higher risk of acquiring HIV. Despite the increasing availability of daily oral pre-exposure prophylaxis (PrEP) for HIV prevention, knowledge on PrEP use during pregnancy and postpartum periods at antenatal care (ANC) facilities remains inadequate. Methods Data from HIV-uninfected pregnant women in Cape Town, South Africa, were used in this study. These women aged 16–24 years were enrolled in the PrEP in pregnancy and postpartum (PrEP-PP) cohort study during their first ANC visit. Using the PrEP cascade framework, the outcomes of the study were PrEP initiation (prescribed tenofovir disoproxil fumarate and emtricitabine at baseline), continuation (returned for prescription), and persistence [quantifiable tenofovir diphosphate (TFV-DP) in dried blood samples]. The two primary exposures of this study were risk perception for HIV and baseline HIV risk score (0–5), which comprised condomless sex, more than one sexual partner, partner living with HIV or with unknown serostatus, laboratory-confirmed sexually transmitted infections (STIs), and hazardous alcohol use before pregnancy (Alcohol Use Disorders Identification Test for Consumption score ≥ 3). Logistic regression was used to examine the association between HIV risk and PrEP, adjusting for a priori confounders. Results A total of 486 pregnant women were included in the study, of which 16% were “adolescents” (aged 16–18 years) and 84% were “young women” (aged 19–24 years). The adolescents initiated ANC later than the young women [median = 28 weeks (20–34) vs. 23 weeks (16–34), p = 0.04]. Approximately 41% of the AGYW were diagnosed with sexually transmitted infection at baseline. Overall, 83% of the AGYW initiated PrEP use during their first ANC. The percentage of PrEP continuation was 63% at 1 month, 54% at 3 months, and 39% at 6 months. Approximately 27% consistently continued PrEP use through 6 months, while 6% stopped and restarted on PrEP use at 6 months. With a higher risk score of HIV (≥2 vs. ≤1), the AGYW showed higher odds of PrEP continuation [adjusted odds ratio: 1.85 (95% CI: 1.12–3.03)] through 6 months, adjusting for potential confounders. Undergoing the postpartum period (vs. pregnant) and having lower sexual risk factors were found to be the barriers to PrEP continuation. TFV-DP concentration levels were detected among 49% of the AGYW, and 6% of these women had daily adherence to PrEP at 3 months. Conclusions AGYW were found to have high oral PrEP initiation, but just over one-third of these women continued PrEP use through 6 months. Pregnant AGYW who had a higher risk of acquiring HIV (due to condomless sex, frequent sex, and STIs) were more likely to continue on PrEP use through the postpartum period. Pregnant and postpartum AGYW require counseling and other types of support, such as community delivery and peer support to improve their effective PrEP use through the postpartum period. Clinical Trial Number ClinicalTrials.gov, NCT03826199.